VARIANT COMPUTER SHELL PROTOTYPING BASED ON POLYPARAMETERIZATION OF MIDDLE SURFACES - V V VANIN; S L SHAMBINA; G I VIRCHENKO (Structural Mechanics of Engineering Constructions and Buildings, 2015)
The paper considers the possibility of using the polyparameterization method for geo- metric modeling of middle surfaces of shells in order to ensure their effective computer pro- totyping. Examples of variant forming of thin-walled spatial building structures were ana- lyzed